Effect of different concentrations of 6-Benzylaminopurine (BAP) on growth of Centella Asiatica (L.) urban cuttings - Yusof, Siti Salwa (2013)
Centella asiatica (pegaga) is an important medicinal plant that has been claimed to possess various healing effect and antioxidant properties. For many years, a lot of commercial and medicinal researches have been carried out on this plant to meet the pharmaceutical demand. Therefore, this experiment was carried out to study the effect of different BAP concentration on the growth of C. asiatica cuttings. The experiment was carried out at the Cell Biology and Genetics Laboratory, Department of Agriculture Technology, Faculty of Agriculture, Universiti Putra Malaysia. The objective of this experiment was to determine the best concentration of BAP for optimizing the growth of Centella asiatica cuttings. The experiment was conducted using Randomized Complete Block Design (RCBD) with five treatments and six replications. The cuttings of C. asiatica were dipped into BAP solution (0.0, 0.5, 1.0, 5.0, 10.0 mg/L) for one hour. Then, they were planted in trays containing perlite. Each plant cutting was supplied with Murashige and Skoog (MS) solution at 20 mL every week. The experiment was carried out for duration of 6 weeks. The number of leaf per cutting, mean root volume, and length of root were recorded as the parameters. Data were analyzed using ANOVA and the means were compared using Tukey test. It was observed that there was no significant difference between all BAP treatments compared with control treatment on mean number of leaf and mean root volume. However, there was significant difference observed on the mean root length between BAP treatments at 5.0 mg/L and 10.0 mg/L.